The Relationship Between Lower-Body and Upper-Body Muscle Power and Smash Accuracy in Men’s Volleyball - Andriansah Andriansah; Feby Elra Perdima; Aziiz Rahman Putra (UNIVED Press, Universitas Dehasen Bengkulu, 2026)
This study aims to determine the relationship between lower-body muscle power and upper-body muscle power and smash accuracy among volleyball club athletes at Dehasen University in Bengkulu. The smash is one of the primary attacking techniques in volleyball, and its success is influenced by various physical factors, including lower-body muscle power and upper-body muscle power. This study employed a quantitative method with a correlational research design. The population of this study consisted of extracurricular volleyball athletes at Dehasen University in Bengkulu. The research sample consisted of 15 athletes selected based on the sampling technique used by the researcher. The research instruments used were the vertical jump test to measure lower limb muscle power, the medicine ball throw to measure upper limb muscle power, and the smash accuracy test to measure smash accuracy ability. Data analysis techniques used the Pearson Product-Moment correlation test to examine the relationship between each independent variable and the dependent variable, as well as multiple correlation to examine the combined relationship of the two independent variables on the dependent variable. The results of the study indicate that there is a significant relationship between lower-body muscle power and smash accuracy, as evidenced by a correlation coefficient of 0.695. There is a significant relationship between upper-body muscle power and smash accuracy, as evidenced by a correlation coefficient of 0.751. Furthermore, there is a significant relationship between lower limb muscle power and upper limb muscle power combined with smash accuracy, as indicated by a multiple correlation coefficient (R) of 0.839; the significance test results show that the calculated F-value (Fhitung) of 14.30 is greater than the critical F-value (Ftable) of 3.89 at a 5% significance level. Based on the research results, it can be concluded that lower limb muscle power and upper limb muscle power have a significant relationship with smash accuracy among volleyball club athletes at Dehasen University, Bengkulu. The better the lower limb muscle power and upper limb muscle power possessed by the athletes, the better the resulting smash accuracy.